Parameters characterization of dielectric materials samples in microwave and millimeter-wave bands - Pérez-Escribano, Mario; Márquez-Segura, Enrique (IEEE Transactions on Microwave Theory and Techniques, 2021)
In this work, an optimized broadband method using multilayer transmission lines to characterize dielectric permittivity and loss tangent of material samples is presented. For this purpose, a microstrip line loaded with a piece of the selected dielectric to be characterized is used. From two-port measurements, and using different length lines, the propagation constant can be obtained. To minimize random errors and to improve the accuracy, an overdetermination of the method increasing the number of lines measured and a criterion to choose the optimal line lengths is considered. First, the measurement method itself is applied to uncovered microstrip lines and an accurate model of the substrate is obtained. Second, the lines are covered with several materials, made by fused deposition modeling (FDM) additive manufacturing technique, such as acrylonitrile butadiene styrene (ABS), polylactic acid (PLA), high impact polystyrene (HIPS), thermoplastic polyurethane (TPU), copolyester (CPE), FLEX, polyethylene terephthalate glycol (PETG), and nylon. A model of the transmission line considering the cover is developed, and an electromagnetic (EM) simulator is used to indirectly determine the cover material electrical parameters. Results show excellent agreement with EM simulations in the 0.1–67-GHz frequency band, so they assess the suitability of the proposed method.
Keywords: Relajación dieléctrica; Broadband measurements; Dielectric materials; EM material characterization; Propagation constant; Transmission line measurements